EVALUATING THE FEASIBILITY OF THE 12L TAX INCENTIVE FOR ENERGY-INTENSIVE INDUSTRIES - Campbell, Kristy; Booysen, W; Vosloo, J C (The South African Journal of Industrial Engineering, 2017)
Section 12L of the South African Income Tax Act (12L) aims to incentivise businesses to become more energy-efficient. However, claiming this benefit is a complex process that can become difficult, time-consuming, and costly if not clearly understood. It is therefore important to evaluate the feasibility of potential 12L applications before any unnecessary expenses are incurred or time is wasted. This article provides a brief overview of 12L and its associated literature before presenting a simplified feasibility evaluation strategy. The strategy consists of three key evaluation steps designed to identify potential issues quickly. The identified issues are linked to specific South African National Standards (SANS) guidelines to ensure that the issues can be resolved in a 12L-compliant manner. The strategy is applied to 47 industrial case studies. Some detailed results are presented to give a practical illustration of how the strategy works. The generalised results are further used to illustrate the potential benefit in time and cost reduction.